PROPERTIES AND APPLICATIONS OF θg*α-CLOSED SETS IN TOPOLOGICAL SPACES - Sakkraiveeranan Chandrasekar; Velusamy Banupriya; Jeyaraman Suresh Kumar (Journal of New Theory)
Abstaract−In this paper we discussed properties and applications of θg*α-closed sets. θg*α- closed sets is introduced by Chandrasekar et al. Moreover we analyze some basic properties and applications of neighbourhoods, limit points, border, frontier and exterior of θg*α-closed sets